Rola klastrów w rozwoju gospodarczym. NutriBioMed: studium przypadku - Darczuk, Alkmena; Łokuciejewska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Clusters in economical development of global economy are a constant element, pattern how to pursue permament innovation; how small and medium companies can effectively operate, develop themselves and achieve strong position on the international market. NutriBioMed is an example of how small companies by acting together in the cluster structure achieve opportunity to arise in market also by cooperating together may become an origin of regional progress. Clusters may influence level of employment, infrastructure, technological growth which are main reasons of economic evolution.
Keywords: rozwój gospodarczy; klastry; NutriBioMed